Analisis Pengaruh Rasio Keuangan, Kepemilikan Manajerial, dan Kepemilikan Institusional terhadap Financial Distress pada Perusahaan Sektor Perdagangan, Jasa, dan Investasi yang Terdaftar di BEI Tahun 2015-2018 - Masita, Ainnun; Purwohandoko, Purwohandoko (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Financial distress causes the company to restructure or even going bankrupt. It means the prediction of financial distress is important to anticipate the occurrence of bankruptcy. This study aimed to determine the effect of financial ratios, managerial ownership, and institutional ownership on financial distress. The independent variables used in this study are the current ratio, debt to assets ratio, return on assets, total assets turnover, managerial ownership, and institutional ownership. This research’s population is sector trade, services, and investment firms listed on the Indonesia Stock Exchange in 2015-2018. It implements purposive sampling techniques and finally obtained 15 firms as samples. The research then is analyzed using logistic regression and calculated using SPSS software version 25. The result showed that debt to assets ratio had a positive significance on financial distress and return on assets had a negative significant effect on financial distress. While the other variables of total assets turnover, current ratio, managerial ownership, institutional ownership don’t have a significant effect on financial distress. Therefore, the companies are expected to pay attention to increasing the value of debt to assets ratio and return on assets to avoid the possibility of financial distress.